2003
DOI: 10.1520/jfs2003109
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Analysis of Human Nuclear and Mitochondrial DNA from Electron Beam Irradiated Envelopes

Abstract: The United States Postal Service is considering methods such as electron beam irradiation to neutralize biological agents sent through the mail. While this is proven to reduce/eliminate pathogenic organisms, it may also degrade human genomic DNA and therefore hinder the ability to garner forensically informative genetic profiles. To determine the effects of electron beam irradiation on DNA typing, 16 white, standard letter-sized envelopes were licked. Half of the envelopes served as nonirradiated controls whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…PCR products were sized by agarose gel electrophoresis (data not shown) and purified using the Qiagen ® QiaQuick PCR amplification kit [23]. To prevent chemical degradation postpurification, purified products were eluted in Qiagen Buffer EB (10mM Tris-Cl, pH 8.5) and stored at −20° C.…”
Section: Purification and Sequencing Of Real-time Pcr Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…PCR products were sized by agarose gel electrophoresis (data not shown) and purified using the Qiagen ® QiaQuick PCR amplification kit [23]. To prevent chemical degradation postpurification, purified products were eluted in Qiagen Buffer EB (10mM Tris-Cl, pH 8.5) and stored at −20° C.…”
Section: Purification and Sequencing Of Real-time Pcr Productsmentioning
confidence: 99%
“…Purified PCR products were sequenced using ABI Big Dye Terminator chemistry with Taq FS polymerase [23]. Due to the shortness of templates (< 100 bp), modifications to the reference protocol were made.…”
Section: Purification and Sequencing Of Real-time Pcr Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA analysis was performed to determine if there was any PCR interference or (Withrow et. al., 2003).…”
Section: Short Tandem Repeats Used In This Studymentioning
confidence: 99%
“…In some instances, gamma radiation was shown to eliminate small amounts of genomic and plasmid DNA [4]. Withrow et al [5] demonstrated that full mitochondrial and nuclear profiles were obtained after beta radiation doses of 29.3 and 51.6 kGy even though it was demonstrated that the radiation significantly reduced the total amount of DNA extracted and that some evidence of degradation was present. Work conducted by Castle et al [6] corroborated this result and showed that the amount of DNA available for profiling is reduced after beta radiation but that 16 STRs (including all 13 CODIS STRs) were detectable after treatment.…”
Section: Introductionmentioning
confidence: 99%